Vertical and horizontal emissions of greenhouse gases from a pineapple (Ananas comosus L. Merr.) tropical peat soil - Jeffary, Alicia Vanessa (2017)
Peat soils are important natural resources. Peat soils have been cleared, developed, and cultivated for large scale plantations such as oil palm due to their positive contribution to Malaysia’s economic growth in agriculture sector. However, these developments contribute to the emissions of greenhouse gases (GHGs). However, concerns by NGOs have been expressed that increasing cultivation of pineapples on peat soils lead to increase in the emissions of harmful greenhouse gases such as carbon dioxide (CO₂), methane (CH₄), and nitrous oxide (N₂O). To date, there were limited information of GHGs emissions from pineapple cultivation and also inadequate data on horizontally and vertically soil GHGs emissions in peat soil profile. Thus, this study was carried out to determine GHGs emissions horizontally and vertically and to quantity horizontal and vertical GHGs emissions from a drained tropical peat soils from a drained tropical peat soils cultivated with pineapple (Ananas comosus (L.) Merr. Horizontal and vertical movements of GHGs were measured from a drained tropical peatland with Ananas comosus (L.) Merr. at Malaysian Agricultural Research and Development Institute (MARDI) Saratok, Sarawak, Malaysia. Soil GHGs flux sampling via closed chamber method (I and L-shaped closed chambers) and was carried out for 24 hours at a 6 hour interval (between 0600 hr to 0600 hr). Soil GHGs flux sampling were carried out once a month in July and august 2015 which represent dry seasons and September and December 2015 which represent wet season. The GHGs concentration was measured using a Gas Chromatography (GC – Agilent 7890A). Tropical peat soils cultivated with Ananas comosus (L.) Merr. contributed to 79.7% of CO₂, 20.1% of N₂O, and 0.2% of CH₄ based on the year basis regardless of the differences in diurnal transportation; horizontal and vertical emission. Soil GHGs were emitted the most through horizontal transportation with 70.84% CO₂, 18.72% N₂O, and 0.19% CH₄ compared to 8.85% CO₂, 1.38% N₂O, and 0.02% CH₄ in vertical transportation. The emission of CO₂ was influenced by depth of water table and temperature. It is generally believed that lowering of peats water table leads to emission of higher CO₂ emission because this process leads to exposure of peat soils to oxidation. Factors influencing N₂O production include peat temperature, soil moisture, water-filled pore space, and nitrogen status of the peat. Seasonal variation in CH₄ flux was higher in the wet seasons due to rainfall; this might have increased the water table of the peat soil. Therefore, it is hoped that from the findings of this study, farmers have an idea regarding the appropriate approach and methodology in managing GHG emissions especially from peat soils and so as to improve the accuracy and subsequently minimize controversies. It is also a hoped that through this study, it will provide insights on farm management procedures in dealing with the emission of the GHG such as the appropriate peat soil land management, fertilization, types of crop to be cultivated and others. Last but not least, information obtained from this study will also give awareness not only to the farmer but also to the societies regarding the controlling of GHG emissions from a drained tropical peat soils cultivated with pineapples.